2017
DOI: 10.1128/jvi.00415-17
|View full text |Cite
|
Sign up to set email alerts
|

Dense Array of Spikes on HIV-1 Virion Particles

Abstract: HIV-1 is rare among viruses for having a low number of envelope glycoprotein (Env) spikes per virion, i.e., ϳ7 to 14. This exceptional feature has been associated with avoidance of humoral immunity, i.e., B cell activation and antibody neutralization. Virus-like particles (VLPs) with increased density of Env are being pursued for vaccine development; however, these typically require protein engineering that alters Env structure. Here, we used instead a strategy that targets the producer cell. We employed fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 87 publications
1
57
0
Order By: Relevance
“…It was possible in our case, however, that the modifications made to the HIV gp150 envelope protein already significantly increased the levels of Env in Gag VLPs to a level that could not be further increased by the replacement of the TM + CT regions with that of the influenza hemagglutinin protein. Various studies have shown that truncation of the HIV Env from gp160 to gp150 increases the levels of expression on the surface of virus particles [10,32]. In addition, the replacement of the native HIV Env leader sequence with other leader sequences has also been shown to increase expression [10,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…It was possible in our case, however, that the modifications made to the HIV gp150 envelope protein already significantly increased the levels of Env in Gag VLPs to a level that could not be further increased by the replacement of the TM + CT regions with that of the influenza hemagglutinin protein. Various studies have shown that truncation of the HIV Env from gp160 to gp150 increases the levels of expression on the surface of virus particles [10,32]. In addition, the replacement of the native HIV Env leader sequence with other leader sequences has also been shown to increase expression [10,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…BN-PAGE analysis showed that Comb-mut-LK trimers were recognized more efficiently and by a greater number of V2 bnAbs than Comb-mut and that the bnAb-Env association was improved further by chemical cross-linking. We note, too, that MPER and gp41 interface bnAbs 10E8, PGT151, and 35O22 potently neutralize Comb-mut-LKQ with high MPNs similar to those for Comb-mut (70), suggesting that this Env is relatively homogeneous throughout the trimer interfaces.…”
Section: Fig 10mentioning
confidence: 61%
“…Thus if HIV-1 virions contain a random assortment of a small number of Env trimers that diffuse slowly or not at all in the membrane, then only a small number of Envs would be available on the small contact surface formed by a roughly spherical virion and a flat cell membrane, whereas more Envs would be available for contacts with a larger contact surface formed by a virion interacting with a concave cell membrane (Figure 1c). Indeed, a recent ET study of murine leukemia virus (MLV) attached to target cells revealed a concave surface on the target cell with ~28 spokes per attached virion [64], a number that would be predicted to be higher than observed for HIV-1 even if HIV-1 were interacting with a concave portion of its target cell because MLV includes more spikes (at least 100 per virion) [65] compared with HIV-1 (7-14 per virion) [52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%